Right to property in Nigeria and power of revocation under the land use act (2016)
The importance of land immovable property is considered very fundamental to (he existence of mankind. Apart from being used for shelter. it is also a significant factor of production. Its ownership in most societies. symbolizes power and affluence. This natural resources is however limited in supply since by its nature fixed. though its value unquantifiable. The demand for land exceeds its availability (supply). hence the need for government Intervention for the purpose of redistribution among individuals who desire it for various purposes. The need to avoid conflicts and protect the weak in the society made government to enact laws to protect such ownership/occupancy. This paper examines in some depth the fundamental right to property. its enforcement and the state power of compulsory acquisition through revocation of right of occupancy. How has the laws. such as the Constitution of the Federal Republic of Nigeria. 1999 (as amended) and the Africa Charter on Human and Peoples' Rights been able to guarantee the fundamental right to property. The paper further takes a cursory look at the procedure for revocation of right of occupancy, compulsory acquisition, compensation and judicial intervention.